Analisis Pengaruh Berat Loler Sliding Terhadap Torsi, Daya Dan Kosumsi Bahan Bakar Pada Motor Metic CVT: Sliding Roller Weight Variations on Torque, Power, and Consumption of CVT Motorcycles - Kadek Ari Setiawan; Ni Made Novia Kusumayani; Nyoman Arya Wigraha (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the effect of sliding roller weight variations on torque, power output, and fuel consumption in automatic motorcycles equipped with a CVT (Continuously Variable Transmission) system. The research object is a 2013 Honda Vario 110cc FI motorcycle. The rollers used include a standard cylindrical roller weighing 13 grams, and sliding rollers with weights of 10 grams, 12 grams, and 15 grams, respectively. The research method employed is experimental, with data collected through dynotest measurements for torque and power, as well as fuel consumption testing within an engine speed range of 3000 – 7000 rpm, with data recorded at five specific points: 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, and 7000 rpm. The results indicate that variations in sliding roller weight affect engine torque and power. In general, all sliding roller variations tested produced higher torque and power compared to the standard roller. Torque testing revealed that increasing the weight of the sliding roller tends to enhance torque at lower engine speeds. The 15-gram sliding roller produced the highest average torque of 20.28 N.m at 3000 rpm, while the 10-gram and 12-gram rollers produced average torque values of 19.82 N.m and 19.81 N.m, respectively. Power testing showed that lighter sliding rollers tend to generate greater power at medium engine speeds. The 10-gram roller yielded the highest average power output of 9.08 HP at 5000 rpm, followed by the 12-gram (8.94 HP) and 15-gram (7.96 HP) rollers. Meanwhile, fuel consumption testing showed that all roller variations exhibited nearly identical consumption patterns at each engine speed, with an average difference of less than 0.015%. Keywords: CVT, sliding roller, torque, power output, fuel consumption, automatic motorcycle